Linking residents’ perceptions of pandemic quality of life with their support for sustainable tourism development in the post-COVID-19 era - Nataša Đorđević; Dimitrovski, Darko; Leković, Miljan; Weeden, Clare (Hotel and Tourism Management, 2022)
The COVID-19 pandemic has changed tourist flows, reducing the number of international tourist arrivals around the world. One of the ways to protect the tourism industry from the ongoing health crisis was through the stimulation of domestic and proximity tourism. During the COVID-19 pandemic in Serbia, domestic tourists were attracted to spa destinations such as Vrnja?ka Banja. Thus, residents of this small-town destination experienced a great influx of tourists, altering their everyday lives. This paper examines the quality of life domains of Vrnja?ka Banja residents during the pandemic and their support for sustainable tourism initiatives in the viable future. Study findings suggest that spirituality and support from friends and general quality of life as identified domains of quality of life during the pandemic emerged as antecedents of support for sustainable tourism. The study contributes to the existing tourism knowledge by acknowledging the capacity of different domains of residents? quality of life in the pandemic context to frame future sustainable tourism initiatives.